2019
DOI: 10.3390/antibiotics8020062
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Year Single-Centre Audit on Antibiotic Resistance of Pseudomonas aeruginosa, Acinetobacter baumannii and Klebsiella pneumoniae Strains from an Intensive Care Unit and Other Wards in a General Public Hospital in Greece

Abstract: Hospital-acquired infections, particularly in the critical care setting, are becoming increasingly common during the last decade, with Gram-negative bacterial infections presenting the highest incidence among them. Multi-drug-resistant (MDR) Gram-negative infections are associated with high morbidity and mortality, with significant direct and indirect costs resulting from long hospitalization due to antibiotic failure. As treatment options become limited, antimicrobial stewardship programs aim to optimize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
5
28
1
Order By: Relevance
“…The results of the present study showed that the resistance levels to carbapenems, β-lactam-containing agents, and tigecycline in E. coli were higher than those in K. pneumoniae; however, E. coli and K. pneumoniae maintained high sensitivity to all the agents. In this study, the resistance rates of E. coli to all the antimicrobial agents in the whole hospital and the ICUs were higher than those reported in other areas, including by CHINET surveillance (5) and in Nanjing (26), Zhengzhou (6), and Greece (31). However, the resistance levels of K. pneumoniae to most of the antimicrobial agents were lower than those reported in these areas.…”
Section: Discussioncontrasting
confidence: 68%
“…The results of the present study showed that the resistance levels to carbapenems, β-lactam-containing agents, and tigecycline in E. coli were higher than those in K. pneumoniae; however, E. coli and K. pneumoniae maintained high sensitivity to all the agents. In this study, the resistance rates of E. coli to all the antimicrobial agents in the whole hospital and the ICUs were higher than those reported in other areas, including by CHINET surveillance (5) and in Nanjing (26), Zhengzhou (6), and Greece (31). However, the resistance levels of K. pneumoniae to most of the antimicrobial agents were lower than those reported in these areas.…”
Section: Discussioncontrasting
confidence: 68%
“…Similarly, antibiotic stewardship decreased the incidence of carbapenem-resistant strains of K. pneumoniae, P. aeruginosa, and A. baumannii from 94 to 6%, 91 to 83%, and 38 to 2.5%, respectively. 8 Feretzakis et al 8 also demonstrated a reciprocal increase in the incidence of nonresistant isolates of above GNB, during the period, when resistant strains were decreasing. Strict surveillance should be followed for the emergence of new resistant pathogens while implementing a new antibiotic protocol.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the incidence of antibiotic resistance in these four gram-negative bacteria is similar to reported by Feretzakis et al for all antibiotics (Aminoglycosides, Fluoroquinolones, B lactam/ B lactamase combinations, and carbapenems) except Colistin. 8 Regarding resistance, in gram-negative bacteria, the antibiotics that have been at the center of research are Cephalosporins, carbapenems, and colistin. An earlier study published from our institute documented the incidence of various antibiotic-resistant bacteria in our CSICU (►Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Pandrug resistant bacteria (PDR) and XDR isolates of A. baumannii have been reported for many years, not only in Polish hospitals, but also globally [9][10][11][12][13]. Infections caused by these strains are a serious therapeutic issue and are particularly common among intensive care unit (ICU) patients, but also appear in people hospitalized in other departments [14][15][16][17][18][19]. It seems that A. baumannii is one of the main etiologic agents of hospital associated infections (HAIs) and epidemic outbreaks in Poland, compared to infections caused by other non-fermenting bacteria (Pseudomonas aeruginosa), which are less frequently reported in our country [9,20,21].…”
Section: Introductionmentioning
confidence: 99%